STUDI PRODUKSI RADIONUKLIDA MEDIS UNTUK GENERATOR 89Sr/90Y DARI HASIL REAKSI 89Rb(p,n)89Sr/90Y PADA SIKLOTRON MEDIK SECARA KOMPUTASI - Hidayat, Yusup; Wardaya, Asep Yoyo; Triadyaksa, Pandji; Setiawati, Evi; Muhlisin, Zaenul; Sumariyah, Sumariyah; Suseno, Jatmiko Endro; Binu Soesanto, Qidir Maulana (BERKALA FISIKA, 2019)
A computational calculation to determine production capacity of 90Y from the results of nuclearreactions 89Rb(p,n)89Sr/90Y from several medical cyclotrons has been carried out. Calculations were used to obtain the target thickness of 89Rb and maximum activity of 90Y on variable energy, time and irradiation currents. Calculations were also carried out to measure the impurity radionuclide activity during the reaction. The results activities of 90Y were obtained through modeling using the SRIM-2013 software and the TENDL-2017 application and calculated using MATLAB software. The results modeling and of calculations can predict the activity of 90Y and it can be used as an initial reference in the radionuclide production process using a cyclotron. The maximum activity of 90Y of 5409.80 mCi with a 10.54 mm-target thickness of 89Rb is generated from a cyclotron which has a 30 MeV proton beam with a 50 Î¼A radiation current beam and 2 hours irradiation time. Using the same proton, current and irradiation time at irradiation energy of 8 MeV, 15 MeV and 22 MeV, the produced activity of 90Y was smaller, there are 552.28 mCi, 2100.39 mCi and 3644.31 mCi. The radioisotope of 90Y can be used in patients with a normal dose of 0.4 mCi / kg body weight, therefore in one production can supply the needs of 104 patients.Keywords: medical cyclotron, calculation and modeling, 90Y activity